Know and grow: A qualitative evaluation of a parent skills training intervention - Goodier, G.; McCormack, J.; Egan, Sarah; Watson, H.; Todd, G.; Treasure, J.; Hoiles, K.; Lister, S.; James, K. (BioMed Central, 2014)
Objective: This qualitative study examined the experience of parents of children and adolescents with eating disorders after having participated in a skills-based training intervention. Method: Participants were interviewed and transcripts were analysed using inductive thematic analysis. Results: Parent responses were organised around key themes of (1) effectiveness and acceptability of the intervention; (2) interpersonal experience of the group process; and (3) feedback on intervention content. Overall, the program was seen by parents to be highly relevant with direct application to supporting their child in home and hospital environments. Discussion: This study reports on preliminary evidence that skillsbased training is acceptable to parents and improves parent functioning including parent self-efficacy, and reduces psychological distress, anxiety, and burden. The study also demonstrated that the intervention can be delivered in a tertiary paediatric treatment setting and it may become cost-effective method for supporting parents and other carers. Future research is required on treatment efficacy and patient outcomes.